IMPLEMENTASI PENCATATAN KETIDAKLENGKAPAN CATATAN MEDIS RAWAT INAP DI RSUD TONGAS: Implementation of Recording Incompleteness of Inpatient Medical Records at RSUD Tongas - Rusdi, Achmad Jaelani; Rauf, Abdur; Faid, Roifatul (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
Hospitals as health service provider institutions need to consistently improve their service quality standards by ensuring that the medical records presented are precise and accurate. Medical record filling is considered quality if each component in the medical record form is filled with comprehensive information. Comprehensive medical records reflect the quality standards of the hospital. This study aims to identify the level of completeness of inpatient medical record documents at RSUD Tongas by applying a quantitative descriptive approach method. Sampling was done based on the Slovin formula from a population of 407 files, and resulted in 80 samples. The results showed that the average completeness based on patient identification reached 100%. The results of the review of the average completeness of important reporting were 96%. The results of the average review of completeness on authentication are 85%. The results of the average review of completeness in documentation are 100%. Medical record documents that are incomplete will be returned to the treatment room or the doctor in charge of the patient.